Comparison of ocular changes in multiple sclerosis and neuromyelitis optica spectrum disorder patients - Wang, Xiaoyue; Bao, Li (Frontiers in Neurology, 2024)
Purpose: To explore ocular changes in patients with MS and NMOSD via SD-OCT and PVEP analysis. Methods: From August 2020 to July 2021, eighty-two patients (164 eyes) diagnosed with MS, 59 patients (118 eyes) diagnosed with NMOSD and 50 healthy controls (100 eyes) were retrospectively selected. SD-OCT and PVEP were performed to compare retinal nerve fibre layer (RNFL) thickness around the optic disc, ganglion cell inner plexiform layer (GCIPL) thickness in the macula and P100 latency and amplitude between the disease groups and the control group. Results: In the NMOSD and MS groups, the thickness of the GCIPL quadrants in eyes with optic neuritis was thinner than that in eyes without optic neuritis, and the amplitude of the P100 wave decreased. In addition, in eyes with optic neuritis, patients with NMOSD have thinner RNFL thicknesses in the temporal and superior quadrants than patients with MS, and the thickness of the GCIPL is thinner in each region. In eyes without optic neuritis, patients with MS have thinner nasal RNFL than do those with NMOSD. Conclusion: SD-OCT and VEP may be useful for monitoring and distinguishing pathological changes in MS and NMOSD patients.